Karangwangi people’s local knowledge of bamboo and its role: Implications for management of cultural keystone species - RUHYAT PARTASASMITA; AZIFAH AN’AMILLAH; JOHAN ISKANDAR; ASEP ZAINAL MUTAQIN; ANNISA ANNISA; NINING RATNINGSIH (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Partasasmita R, An’amillah A, Iskandar J, Mutaqin AZ, Annisa. 2017. Traditional knowledge of bamboo and its role in Karangwangi Village Cianjur, West Java: Implications for management of cultural keystone species. Biodiversitas 18: 275-282. Indonesia has a high diversity of bamboo, with more than 160 species can be found around the country. Nowadays, this plant is rarely planted around rural communities of West Java due to land use conversions and economic reasons. This research is to discuss traditional knowledge of local people of Karangwangi Village, Cianjur, West Java, Indonesia on diversity of bamboo and its role. The qualitative method was used in this study, while the data collection techniques, namely semi structure interview or deep interview and observation participant are applied. The result of study shows that based on the traditional knowledge of Karangwangi people, it has been reviled 13 species of bamboo, e.g., Bambusa blumeana J.A. & J.H. Schultz, Bambusa glaucophylla Widjaja, Bambusa maculata Widjaja, Bambusa vulgaris Schrad. Ex. Wndl. var vulgaris, Bambusa vulgaris Schrad. Ex. Wndl. var. striata, Gigantochloa apus J.A. & J.H. Schultz. Kurz., Gigantochloa atrovilacea Widjaja, Gigantochloa atter (Hassk.) Kurz., Gigantochloa hasskarliana (Kurz.) Backer ex Heyne, Gigantochloa pseudoarundinacea (Steud.) Widjaja, Schizostachyum iraten Widjaja, Schizostachyum sp., and Dinochloa scandens (Blume ex Neese) Kuntze. On the basis of deep interview, these bamboo species have traditionally various used, such as building materials, furnitures, household appliances, working tools, medicine, consumption, traditional musical instruments, traditional game, and decoration. In addition, Bamboo soften feature prominently in the language, ceremonies, and narratives of native peoples, so it can be considered as a cultural icons. The implications of these discussion are with respect to conservation as cultural keystone species. Keywords: Bamboo, biodiversity, cultural keystone species, ethnobiology, Karangwangi